Reliability of water supply from stormwater harvesting and managed aquifer recharge with a brackish aquifer in an urbanising catchment and changing climate. (October 2015) - Clark, R.; Gonzalez, D.; Dillon, P.; Charles, S.; Cresswell, D.; Naumann, B.
Abstract: Recent research shows stormwater harvesting with Managed Aquifer Recharge (MAR) and complementary treatment can deliver safe potable water supplies. To address supply reliability the "WaterCress" hydrological model was used iteratively to simulate runoff, recharge and recovery for different rainfall, catchment and aquifer conditions, and operational scenarios based on the Parafield scheme in Salisbury, South Australia. Using historical rainfall and current catchment and operating conditions, annual demand equating to 12.8% of catchment rainfall could be met with 99.5% volumetric reliability. Using projected rainfalls from a high emission climate scenario resulted in a smaller harvestable volume decline than the increase expected from urban consolidation. Freshwater storage depletion in the brackish aquifer was expected to reduce the supply by 10% with 99.5% reliability compared with zero depletion. This simple generic modelling approach was useful for estimating reliability of stormwater MAR systems to assist planning and design and provide a basis for investor confidence. Highlights: Annual demand equating 12.8% catchment rainfall met with 99.5% reliability. 7% less rainfall under climate change reduced supply by 3%. 20% impervious area increase resulted in 8% more supply. Increased supply volumes through urbanisation would offset effects of climate change. Aquifer losses through mixing reduced supply by 10% due to short storage times.